HBIM (modelowanie informacji na temat budynku historycznego) specyfikacja cyfrowej rekonstrukcji zniszczonego dziedzictwa kulturowego na przykładzie Nowej Synagogi we Wrocławiu - Agajew, Sima (Lodz University of Technology. Press, 2020)
The use of HBIM technology in the reconstruction of damaged historical objects allows to create a digital model and database for the said object, which becomes a source of information for this building, but also for future reconstruction of historical objects.

Zastosowanie technologii HBIM w rekonstrukcji zniszczonych obiektów historycznych pozwala stworzyć cyfrowy model oraz bazę danych dla omawianego obiektu, która staje się źródłem informacji dla omawianego budynku, ale również dla przyszłych rekonstrukcji obiektów historycznych.
HBIM (Historic Building Information Modelling) specifi cation for digital reconstruction of destroyed cultural heritage on the example of The New Synagogue in Breslau/Wrocław, Poland
eng.abstract
Keywords: HBIM; reconstruction; heritage; HBIM; rekonstrukcja; dziedzictwo